САБЗАВОТ ЭКИНЛАРИНИ ИФОДАЛОВЧИ ФИТОНИМЛАР ВА УЛАРНИНГ МАВЗУИЙ ТАСНИФИ (Scientific journal of the Fergana State University, 2023)
This article is about special names of Uzbek vegetables and subdividing thematically types of phitonims and analyzing their lingual motivational-nominative peculiarities.